Thick pore walls mesoporous silicon composites based on phosphomolybdic acid: An efficient catalyst for oxidation desulfurization reaction. (February 2023) - Chen, Xifeng; Luo, Junjie; Khan, Sara; Shi, Ruiping; Li, Pengyang; Shi, Songlin; Hu, Jianglei; Shi, Fengwei
Abstract: In this paper, phosphomolybdic acid (HPMo) solution was chosen as a synthetic medium and active ingredient to replace hydrochloric acid, and the thick porous wall silicon composite based on HPMo (HPMo@OMS) was prepared by the one-step co-condensation method, which simplified the preparation process and improved the stability of the molecular sieve framework structure. The composite materials have the same ordered 2D hexagonal mesoporous structure as SBA-15. Compared to the traditional SBA-15 loaded HPMo (HPMo@SBA-15) synthesized in hydrochloric acid solution, the characterization results showed that the pore wall thickness of HPMo@OMS is about 2 nm thicker than the HPMo@SBA-15. Under mild experimental conditions, the catalyst has high desulfurization activity, and the removal rate of sulfur-containing substrate reaches 100%. In addition, after 10 desulfurization cycles, the Mo content of the composites recovered by centrifugation 13.74HPMo@OMS was only 1.67% by ICP-AES, the results after ten cycles of experiments showed that the removal rate of DBT could still reach 93.5%. Graphical abstract: Image 1 Highlights: One-step co-condensation method with easy preparation to improve atomic economy. Taking phosphomolybdic acid as acidic medium is consistent with green chemistry idea. The increase in pore wall thickness enhances the catalytic stability of the catalyst. Highly efficient catalytic oxidation desulfurization performance.